Soil respiration in Mexico: Advances and future directions. - Cueva, Alejandro; Robles Zazueta, Carlos A.; Garatuza Payan, Jaime; Yépez, Enrico A. (REVISTA TERRA LATINOAMERICANA, 2016)
Soil respiration (RS) is a CO2 efflux from the soil to the atmosphere defined as the sum of autotrophic (respiration by roots and mycorrhizae), and heterotrophic (respiration of microorganisms that decompose fractions of organic matter and of soil fauna) respiration. Globally, RS is considered to be the second largest flux of C to the atmosphere. From published literature it is clear that its main controls are soil temperature, soil moisture, photosynthesis, organic matter inputs and soil biota composition. Despite its relevance in C cycle science, there have been only twenty eight studies in Mexico in the last decade where direct measurement of gas exchange was conducted in the field. These studies were held mostly in agricultural and forest ecosystems, in Central and Southern Mexico where mild subtropical conditions prevail. However, arid, semi-arid, tropical and wetland ecosystems may have an important role in Mexico’s CO2 emissions because of their extent and extensive land use changes. From the twenty eight studies, only two provided continuous measurements of RS with high temporal resolution, highlighting the need for long-term studies to evaluate the complex biophysical controls of this flux and associated processes over different ecological succession stages. We conclude that Mexico represents an important opportunity to understand its complex dynamics, in national and global context, as ecosystems in the country cover a wide range of climatic conditions. This is particularly important because deforestation and degradation of Mexican ecosystems is rapidly increasing along with expected changes in climate.